Pharmacokinetics and enterohepatic circulation of jervine, an antitumor steroidal alkaloid from Veratrum nigrum in rats - Bingjing Zheng; Caihong Wang; Wenwen Song; Xiaoxia Ye; Zheng Xiang (Elsevier, 2019)
Jervine, a novel steroidal alkaloid from Veratrum nigrum L., exhibits both antitumor effect and potential toxicity. The aim of study was to characterize the pharmacokinetic behaviors and enterohepatic circulation of jervine in rats. A rapid and simple ultra-high performance liquid chromatography-tandem mass spectrometric method was developed and validated for quantification of jervine and alpinetin (internal standard) in rat plasma. After extraction from rat plasma by a simple protein-precipitation method, the analyte was separated on a C18 column (2.1 mm × 50 mm, 1.7 μm) using water with 0.1% formic acid and acetonitrile as the mobile phase delivered at a flow rate of 0.4 mL/min. Jervine and alpinetin were determined in the positive mode with multiple reaction monitoring (MRM) of the ion transitions at m/z 426.3 → 108.8 and m/z 271.0 → 166.9, respectively. Molecular docking method was used to investigate the binding of jervine to p-glycoprotein and dehydroepiandrosterone sulfotransferase. The method was well validated within acceptance limits including specificity, matrix effect, recovery, precision, accuracy, and stability, and was successfully applied to the pharmacokinetic study of jervine after oral and intravenous administration to rats. Jervine presented a small volume of distribution, fast absorption, high oral bioavailability, and enterohepatic circulation. The enterohepatic circulation was first observed in veratrum alkaloids, and was further investigated by molecular docking studies, which was related to the binding of jervine to p-glycoprotein and dehydroepiandrosterone sulfotransferase. The pharmacokinetic properties and enterohepatic circulation of jervine in rats provided a significant basis for the drug-drug interaction and toxicity study in the future. Keywords: Jervine, UPLC-MS/MS, Pharmacokinetics, Enterohepatic circulation